Education on Making Bay Leaf Tea for Gout Therapy Arthritis in Cadres in Klapagading Kulon Village, Wangon District, Banyumas Regency - Adhelia Clarysha; Wasis Eko Kurniawan; Madyo Maryoto (Jurnal Multidisiplin Sahombu, 2025)
The community service program, titled "Bay Leaf Tea Education for Gout Arthritis Therapy for Cadres in Klapagading Kulon Village, Wangon District, Banyumas Regency," addresses the significant health problem of gouty arthritis, particularly among the elderly. Gouty arthritis, characterized by severe joint pain, swelling, and redness, is often caused by high uric acid levels due to excessive purine consumption and a lack of public knowledge regarding its management. This problem is prevalent in Klapagading Kulon Village, where 52 elderly people suffer from gouty arthritis, and local cadres lack sufficient knowledge to effectively address it. The choice of this topic is crucial because bay leaves (Syzygium Polyanthum Wight) have known diuretic and analgesic properties, capable of lowering uric acid levels by increasing urine production. They also contain antioxidants and various beneficial compounds such as tannins and flavonoids. The program aims to increase cadres' knowledge about preparing bay leaf tea for gouty arthritis therapy and their interest in disseminating this information to the elderly. The methodology involved pre-testing, health education through lectures, discussions, and live demonstrations of bay leaf tea preparation, followed by post-testing. The results showed a substantial increase in cadre knowledge, with the average post-test score increasing to 95.5 from a baseline of 68.8, and all nine participating cadres achieving the 'good' category. This demonstrates the effectiveness of the educational methods used and the high enthusiasm of the cadres. The program successfully improved cadres' understanding and practical skills, highlighting the importance of utilizing local herbal remedies for non-pharmacological gout management. This enhanced knowledge empowered cadres to provide valuable health information to the elderly in their communities.